Percepatan Pemulihan Ekonomi Pasca Pandemi di Kota Tangerang Melalui Warung Digital - Heri Satrianto; Agus Kusnawan; Toni Yoyo; Eso Hernawan; Andy Andy; Rr. Dian Anggraeni; Rina Sulistiyowati (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This research aims to investigate the role of digital cafes in accelerating economic recovery in Tangerang City after the COVID-19 pandemic. Using a mixed method of interviews, surveys and analysis of local economic data, this research found that the adoption of digital stalls provides significant benefits in increasing market access, operational efficiency and consumer reach for stall owners, while consumers also benefit in terms of ease of shopping and access to a wider variety of products. The challenges and obstacles faced by digital shop owners are also identified, and efforts to support the development of digital shop owners as a motor for post-pandemic economic recovery are also discussed. In conclusion, this research provides valuable insight into the important role of digital cafes in supporting local economic recovery in Tangerang City, which is expected to become the basis for more effective policies in supporting the micro and small economic sectors in the future.